On the maximum modulus points of entire and meromorphic functions and a problem of Erdos - I. I. Marchenko (Математичні Студії)
Two conjectures concerning the number of maximum modulus points of an entire and a meromorphic function on the circle {z:|z|=r} are presented and discussed.